The Conservation of Jernang Rattan (Daemonorops Draco) By Anak Dalam tribe In Jebak Village, Batanghari, Jambi Province - Sulasmi, Iik Sri; Budiastuti, Sri; Sutarno, Sutarno; Rosyani, Rosyani (LPPM Universitas Jambi, 2020)
Conservation of Jernang Rattan (Daemonorops dracoWilld.) in Jebak Forest, Batanghari, Jambi is not well documented. It is noted that fruit of D. draco is the best income source for Anak Dalam Jambi people since 1624. They harvest fruit of D. draco as much as they need. The Jebak forest is an open access, so all the people of Anak Dalam Jambi Tribe have the same right and responsibility on the forest. However, almost 70% of Jebak Forest area has been degraded because of illegal logging. This is the reason why people of Suku Anak Dalam, try to cultivate D. draco by growing 30 clumps of this species in their rubber plantation. The aim of their activity is to conserve D. draco at their forest. Based on the recent situation, research study of jernang rattan conservation in Jebak Forest was conducted. The research method was semi structural interview. All data were analyzed descriptively. The results showed that the conservation and cultivation of D. draco in Jebak Forest was very difficult because the availability of seeds was not sufficient for root stocks.